Оцінка результатів використання ESG проектів - Лагодієнко, Олег Вікторович (Національний технічний університет "Харківський політехнічний інститут", 2024)
У статті досліджено питання оцінки результатів впровадження ESG проектів у різних галузях економіки. Проаналізовано основні проблеми, з якими стикаються організації при реалізації ESG ініціатив, включаючи неадекватність методологічних підходів до оцінки ефективності та різноманітність стандартів. Охарактеризовано основні аспекти впливу ESG проектів на екологічний, соціальний та економічний розвиток. Розроблено комплексну методологію оцінки результатів ESG ініціатив, що враховує ключові показники ефективності (KPI) у різних сферах діяльності. Запропоновано рекомендації для підвищення ефективності впровадження ESG проектів, що сприятиме досягненню стійкого розвитку підприємств. Проаналізовано різноманітні виклики, з якими стикаються організації, такі як високі витрати на впровадження, опір змінам всередині організації та відсутність належного досвіду. Також розглянуто невизначеність впливу ESG проектів на фінансові результати компаній. Розраховано зведений індекс ESG проектів для підприємств агропромислового комплексу України, що дозволило порівняти ефективність їх впровадження та визначити лідерів і відстаючих у галузі сталого розвитку.

The article explores the issue of evaluating the outcomes of implementing ESG (Environmental, Social, and Governance) projects across various economic sectors. It analyzes the main problems organizations face when implementing ESG initiatives, including inadequate methodological approaches to performance evaluation and the diversity of standards. The primary aspects of ESG projects' impact on environmental, social, and economic development are characterized. A comprehensive methodology for assessing the results of ESG initiatives has been developed, considering key performance indicators (KPIs) across different areas of activity. Recommendations are proposed to improve the efficiency of ESG project implementation, contributing to the sustainable development of enterprises. The study delves into the various challenges that organizations encounter, such as high implementation costs, resistance to change within the organization, and the lack of necessary experience and expertise. Additionally, it addresses the uncertainty regarding the impact of ESG projects on companies' financial performance. By calculating a composite ESG index for agro-industrial enterprises in Ukraine, the research allows for comparing the effectiveness of ESG project implementation and identifying leaders and laggards in the field of sustainable development. The study also underscores the role of independent experts in conducting external audits of results and obtaining certification from recognized organizations to confirm compliance with ESG standards. Continuous improvement of ESG projects involves implementing mechanisms for regular monitoring and updating goals and KPIs in response to changes in the external environment and internal processes. The practical implications of this research are significant for business leaders, investors, policymakers, and all stakeholders aiming to enhance responsibility and sustainability in their operations. The insights provided in this article can help organizations improve the added value created by ESG projects and identify steps necessary to achieve maximum results.
Evaluation of the results of esg project implementation
Keywords: ESG проекти; оцінка ефективності; стійкий розвиток; корпоративна соціальна відповідальність; екологічний вплив; соціальний вплив; економічний розвиток; агропромисловий комплекс; ключові показники ефективності (KPI); зведений індекс ESG; ESG projects; efficiency assessment; sustainable development; corporate social responsibility; environmental impact; social impact; economic development; agro-industrial complex; key performance indicators (KPIs); ESG composite index